A mixed-methods study of examining the concerns of Saudi Arabian middle and secondary school teachers in adopting the Future Gate Learning Management System: a transformation to digital learning - Masmali, Abdullah Essa (Kansas State University, 2020)
The purpose of this mixed-method study was to examine the concerns of teachers in middle and secondary schools as they began to implement the Future Gate LMS in Saudi Arabia. A sample of 1045 teachers participated in this study, who represent teachers from schools selected by the Ministry of Education to implement the transformation to digital learning through the Future Gate LMS project. The study examined teachers’ concerns through the lens of the Concern Based Adoption Model (CBAM) framework. The data in this sequential mixed-method study were obtained through two phases. The first phase was quantitative data through the Stage of Concern Questionnaire (SoCQ) and the second phase was qualitative data through an open-ended question on the SoCQ as well as semi-structured interviews. The results from the SoCQ indicated that teachers in the middle and secondary schools who were selected to implement the Future Gate LMS were in the early concern stages. The highest percentile score was Stage 0 Unconcern 87% followed by Stage 1 Personal 84%, Stage 2 Informational 83%, and Stage 3 Management 73%. The lowest percentile score was in Stage 4 Consequences 54% followed by Stage 5 Collaboration 59% and Stage 6 Refocusing 69%. A one-way MANOVA test revealed a statistically significant difference between teachers’ stages of concerns and their gender and type of degree. It also revealed statistically significant differences between teachers’ stages of concerns and their technographic characteristics (prior experience in educational technology use, type of professional development in educational technology, duration of professional development in educational technology, type of professional development in Future Gate LMS, and duration of professional development in Future Gate LMS). One-way MANOVA also revealed statistically significant differences between teachers’ stages of concerns and technology availability in the classroom (technology in the classroom and Internet access in the classroom). The qualitative data analysis indicated that the top three concerns of teachers were centered around technology and Internet in the school, Future Gate LMS activation, and how students deal with Future Gate LMS. This study contributes to the literature to understand teachers’ needs for successfully implementing innovations. Results obtained from this study are important for all stakeholders so that they can understand teachers’ concerns regarding adopting the transformation to digital learning in Saudi Arabia as it is an important project for the Saudi Arabia 2030 vision.
Keywords: Future Gate Learning Management System; Concern Based Adoption Model (CBAM); Middle and high school in Saudi Arabia; eLearning; Teachers; Educational technology